Survey of intestinal helminths collected from pet rodents in México - Panti May, Jesús Alonso (2017)
In this survey, intestinal helminths from pet rodents in Mérida, México, were analyzed. A total of 46 mice Mus musculus, 28 hamsters Mesocricetus auratus, 23 rats Rattus norvegicus, and 1 gerbil Meriones unguiculatus were purchased from six pet shops and one black market for wildlife in the city of Mérida. The overall prevalence of helminths in rodents was 61.2% (60/98). Six species of helminths were identified: the zoonotic cestode Rodentolepis nana, and the nematodes Aspiculuris tetraptera, Dentostomella translucida, Syphacia obvelata, Syphacia mesocriceti, and Syphacia muris. Of the 60 infected rodents, 25 (41.7%) harbored 2 or 3 species of helminths. Rodentolepis nana was found in 4.3% of mice and 17.9% of hamsters. This is the first report of infection with S. muris in pet rats. Considering the close physical contact between pet rodents and humans, the presence of R. nana in pets represents a potential risk of transmission, especially to children and immunocompromised individuals.